Evaluation of Medicinal Plants Through Fish Feed Against Bacterial Fish Disease (Progressive Agriculture, 2013)
Experiments were conducted maintaining under aquarium and pond conditions using feed containing medicinal plants/extracts was evaluated on artificially and naturally infected fish with bacterial pathogens. When the fish were exposed to high bacterial pathogens Aeromonas hydrophila Ah-11, Pseudomonas fluorescens Pf-13 and Edwardsiella tarda Et-70, recovery of the infected fish varied with the pathogens challenged and feed treatments. Fish feed containing bulb extract of Allium sativum (3% feeding) showed significantly (p